Evaluation in media discourse : analysis of a newspaper corpus - Bednarek, Monika (Corpus and discourse. Research in corpus and discourse., 2006)
Evaluation is the linguistic expression of speaker/writer opinion, and has only recently become the focus of linguistic analysis. This book presents the first corpus-based account of evaluation; one hundred newspaper articles collated to form a 70,000 word comparable corpus, drawn from both tabloid and broadsheet media. The book provides detailed explanations and justifications of the underlying framework of evaluation, as well as demonstrating how this is part of the larger framework of media discourse. Unlike many other linguistic analyses of media language, it makes frequent reference.